Factors influencing the implementation of electronic records and information management: A case study in military service in Malaysia. (19th September 2019) - Abdullah, Azlan Long; Mohammad Yusof, Zawiyah; Mokhtar, Umi Asma
Abstract : Purpose: The purpose of this paper is to explore, identify and gain insight into factors related to electronic records and information management (e-RIM) issues and their influence on the implementation of e-RIM initiative in military service in Malaysia. This exploration was conducted via a literature review and case study. Design/methodology/approach: This study adopted a qualitative approach and used a case study involving two army departments in Malaysia. Interviews triangulated by document content analysis and observations were used for data collection. The data were analysed using a directional content analysis approach. Findings: This study reveals that people, organizations, technology and processes are the interrelated contexts underlying e-RIM issues which inevitably influence the implementation of e-RIM initiatives. Competency and leadership, governance structure, culture and strategic planning, technology development and record-keeping process are the main factors impacting such efforts, in turn forming potential obstacles for organizations implementing such initiatives. Research limitations/implications: The research approach and design adopted and the sample size were insufficient for generalization of the findings. Practical implications: This study shows that e-RIM initiatives pose greater challenges related to various issues that cause difficulties in improving and implementing the initiative. Thus, it is crucial for organizations to ascertain and comprehend the factors that influence e-RIM initiatives prior to formulating strategies and approaches in addressing those factors, which would in turn affect the implementation of e-RIM initiatives. Originality/value: This study provides insights into the fundamental factors embracing the e-RIM issues which influence the initiatives, and thereby fosters further discussion and research in the subject matter in Malaysia.